HUBUNGAN STATUS GIZI DAN KONSUMSI FAST FOOD TERHADAP KEJADIAN DISMENORE PADA REMAJA PUTRI DI SMA NEGERI 2 RAMBAH HILIR - Nasriyah, Isom; Sulistiawati, Wiwin; Febrianti, Duma (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2025)
Nutrition is a substance that functions as a building component in the human body so that it can maintain and repair the tissue function of the human body itself. Consumption of fast food is food that can be processed and served in a short time and easily. Dysmenorrhea is lower abdominal pain during menstruation which is usually accompanied by other symptoms such as sweating, headaches, diarrhea, and vomiting. The purpose of this study was to determine the Relationship Between Nutritional Status and Fast Food Consumption and the Incidence of Dysmenorrhea in Adolescent Girls at SMA Negeri 2 Rambah Hilir. The methodology of this study used a Cross Sectional Design. The population in this study was 252 adolescent girls and the sample in the study was 202 adolescent girls. The sample selection technique used Simple Random Sampling. Data were analyzed using the Chi-Square test. The results of the study showed that there was no relationship between nutritional status and the incidence of dysmenorrhea in adolescent girls with a p-value of 0.388, which means the p-value>0.05 and there was a relationship between fast food consumption and the incidence of dysmenorrhea in adolescent girls with a p-value of 0.045, which means the p-value <0.05, OR= 2.43 (1.09-5.41). So it can be concluded that there is no significant relationship between nutritional status and the incidence of dysmenorrhea and there is a relationship between fast food consumption and the incidence of dysmenorrhea. Suggestions need to be made for cooperation between schools, health centers, health agencies by conducting health promotions about the importance of maintaining nutritional status and fast food consumption on the incidence of dysmenorrhea.